Real-World Outcomes of Adalimumab Treatment for Moderate and Severe Psoriasis in Korean Patients (RAPSODI Study) - Kim, Dong Hyun; Son, Sang Wook; Jeong, Ki-Heon; Ahn, Jiyoung; Lee, Eun-So; Kim, Il-Hwan; Lee, Un Ha; Park, Hai-Jin; Ko, Joo Yeon; Kim, Byung-Soo; Kim, Jin Ju; Rashid, Javed; et al. (Annals of Dermatology, 2023)
Psoriasis imposes a significant treatment burden on patients, particularly impacting well-being and quality of life (QoL). The psychosocial impact of psoriasis treatments remains unexplored in most patient populations. To assess the impact of adalimumab on health-related QoL (HRQoL) in Korean patients with psoriasis. This 24-week, multicenter, observational study, assessed HRQoL in Korean patients treated with adalimumab in a real-world setting. Patient-reported outcomes (PROs) including European Quality of Life-5 Dimension scale (EQ-5D), EQ-5D VAS, SF-36, and DLQI were evaluated at week 16 and 24, versus baseline. Patient satisfaction was assessed using TSQM. Among 97 enrolled patients, 77 were assessed for treatment effectiveness. Most patients were male (52, 67.5%) and mean age was 45.4 years. Median baseline body surface area and Psoriasis Area and Severity Index (PASI) scores were 15.00 (range 4.00~80.00) and 12.40 (range 2.70~39.40), respectively. Statistically significant improvements in all PROs were observed between baseline and week 24. Mean EQ-5D score improved from 0.88 (standard deviation [SD], 0.14) at baseline to 0.91 (SD, 0.17) at week 24 ( =0.0067). The number of patients with changes in PASI 75, 90, or 100 from baseline to week 16 and 24 were 65 (84.4%), 17 (22.1%), and 1 (1.3%); and 64 (83.1%), 21 (27.3%), and 2 (2.6%), respectively. Overall treatment satisfaction was reported, including effectiveness and convenience. No unexpected safety findings were noted. Adalimumab improved QoL and was well-tolerated in Korean patients with moderate to severe psoriasis, as demonstrated in a real-world setting. Clinical trial registration number (clinicaltrials.gov: NCT03099083).